Common Bean Germplasm Molecular Analysis: A Biotechnological Approach for Breeding - Galván, Marta Zulema (2010)
Argentina, which is a major producer of common bean (Phaseolus vulgaris L.), represents the southern most limit of the Andean diversification center of the species. The diverse environmental conditions of these places and human selection favored the development of a great variability of wild beans and landraces, which is endangered due to the destruction of habitats by forest exploitation and agriculture. Information on the variability of these resources is essential to set conservation strategies and design breeding programs aimed at enlarging the genetic base of commercial beans. This work is an overview of the marker-based studies on landraces and wild bean genetic diversity, with special emphasis on Argentinean beans, as a first step for the optimal exploitation of the naturally available bean genetic resources, to generate new traits and improve crop performance. The identification of diversity and hybridization between populations is enhanced by the application of the new tools and the information generated by bean genomic research. Gene flow, which appears to occur fairly frequently in bean, has to be studied in more detail in this region in order to facilitate the transfer of useful alleles from the unexploited germplasm to improved lines, broadening the genetic diversity available for breeding. Some resistance gene analogs (RGAs) have been described within the Andean gene pool and only a few have been functionally characterized or linked to a phenotype. Therefore, a strategy for the exploitation of bean germplasm variability based on the detection of RGAs is also mentioned, though more work should be devoted at identifying these sequences in Andean landraces and wild beans.